2018
DOI: 10.1002/cnma.201700371
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Mechanical Response of Luminescent Dithiol‐Protected Ag29(BDT)12(TPP)4 Cluster Crystals

Abstract: Atomically precise clusters of noble metals are considered to be an important class of advanced materials. Crystals of these clusters composed of inorganic cores and organic ligands are fascinating owing to their tunable and unique properties. Understanding their mechanical properties can give more insight into the design of nanocluster‐based devices. Here, we probe the mechanical response of single crystals of Ag29(BDT)12(TPP)4 cluster (BDT=1,3 benzenedithiol, TPP=triphenylphosphine) under both quasi‐static a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Metal nanoclusters have attracted more and more attention due to their structural properties and potential applications. Previous studies have demonstrated that the optical properties of rod-like metal nanoclusters were impacted by their longitudinal electronic structures. However, it remains unclear whether the optical properties of metal nanoclusters can be manipulated by longitudinal ligand modifications. In addition, dithiolated metal nanoclusters are rarely reported, and the single-dithiolate substitution has not been reported, to the best of our knowledge. These issues inspired our enthusiasm for this study.…”
mentioning
confidence: 88%
“…Metal nanoclusters have attracted more and more attention due to their structural properties and potential applications. Previous studies have demonstrated that the optical properties of rod-like metal nanoclusters were impacted by their longitudinal electronic structures. However, it remains unclear whether the optical properties of metal nanoclusters can be manipulated by longitudinal ligand modifications. In addition, dithiolated metal nanoclusters are rarely reported, and the single-dithiolate substitution has not been reported, to the best of our knowledge. These issues inspired our enthusiasm for this study.…”
mentioning
confidence: 88%
“…114 Sugi et al have experimentally probed the mechanical response of cubic Ag 29 (BDT) 12 (TPP) 4 SCs (abbreviated here as “Ag 29 C”; BDT = 1,3-benzenedithiol, TPP = triphenylphosphine) and indeed found a ligand interaction-induced softness of the SCs. 240 In a follow-up study on these dithiol-stabilised Ag 29 NCLs of cubic or trigonal polymorphs (Ag 29 T), monothiol-stabilised, trigonal Ag 46 (Ag 46 T) and their monoclinic Ag 40 co-crystals (Ag 40/46 M), differences in the Young's modulus ( E r ) and hardness ( H ) were investigated (Fig. 15a and b).…”
Section: A Personal View Of the Fieldmentioning
confidence: 99%
“…The archives of molecular clusters are rich with exciting properties, and therefore, the resulting cluster-assembled solids (CASs) hold the promise of high tunability in a range of material properties. The combination of atomic precision and intercluster interactions in CASs can result in novel collective properties, including tunable electrical transport, mechanical properties, , magnetism, , and luminescence, , which have been explored only to a limited extent.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies of atomically precise Ag 44 CASs suggest the existence of similar ligand-flexure-induced softness . The mechanical response of Ag 29 CAS had been probed by nanoindentation, and the softness of the material was attributed to the protecting ligands . This implies that a correlation between mechanical properties and structures could exist in CASs as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation